Hepatitis E Virus Genotype 3 in Sewage and Genotype 1 in Acute Hepatitis Cases, Israel - Ram, Daniela (Am J Trop Med Hyg, 2016)
Hepatitis E virus (HEV) is an emerging infectious agent in developed countries. HEV genotypes 1 (G1) and 3 (G3) have been identified in environmental and clinical samples in Europe. In Israel, the overall prevalence of anti-HEV IgG antibodies was found to be 10.6%; however, reports of HEV infection are scarce. In this study, the presence of HEV in Israel was investigated using 169 sewage samples from 32 treatment facilities and 49 samples from acute hepatitis patients, all collected between 2013 and 2015. Fourteen sewage samples, from Haifa (11/18 samples), Tel Aviv (2/29 samples), and Beer Sheva (1/17 samples), regions with good sanitary conditions and middle-high socioeconomic populations, were HEV positive. Among the patient samples, 6.1% (3/49) were HEV positive, all returning travelers from India. Genotype analysis revealed G1 HEV in patients and G3 HEV sequences in sewage. Evidence that HEV could be establishing itself in our region may justify more active surveillance to monitor its spread.